Work-Life Balance dan Job Satisfaction Terhadap Organizational Citizenship Behavior : Peran Mediasi Work Engagement - Hasibuan, Jasman Saripuddin; Jufrizen, Jufrizen; Farisi, Salman (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Purpose – This study examines and analyses the effect of work-life balance and job satisfaction on organisational citizenship behaviour through employee engagement in private hospitals in Medan.Methodology – This research uses a quantitative approach. This research was conducted at several Type B Private Hospitals in Medan City. This study collected 200 responses from nurses in various public hospitals in Medan. Of these, 169 questionnaires were deemed suitable for analysis. In this study, data were collected using a questionnaire with a Likert scale. The data analysis technique used was Structural Equation Modelling with the Partial Least Squares (PLS-SEM) approach. Findings – The results of this study indicate that work-life balance and job satisfaction are positively and significantly related to employee engagement. The results also show that work-life balance, job satisfaction, and employee engagement significantly positively affect organisational citizenship behaviour. The results also show that employee engagement mediates the effect of Work-Life Balance and Job Satisfaction on organisational citizenship behaviour at several Type B Private Hospitals in Medan.Originality/Novelty – This study examines work-life balance and job satisfaction as more comprehensive predictors of organisational citizenship behaviour and then explicitly explores the importance of employee engagement as a mediator in the relationship between work-life balance and job satisfaction with organisational citizenship behaviour.Implications – This study has shown that employee engagement mediates the effect of work-life balance and job satisfaction on organisational citizenship behaviour. Recommendations for further research include analysing or using organisational citizenship behaviour variables as mediating variables, not dependent variables.